PERBANDINGAN WAKTU OPTIMAL PEMBERIAN FENTANYL 1,5 Î¼g/kgBB UNTUK MENGURANGI RESPON HEMODINAMIK PADA INTUBASI ENDOTRAKHEAL - , Guntur Muhammad Taqwin; , dr. I.G. Ngurah Rai Artika, Sp.An-KAKV, KAR ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Either Laringoscopy and Endotracheal Intubation are frequently common done in general anesthesia, however Laringoscopy and Endotracheal Intubation actions firmly provoke sympathetic either sympatoadrenal activities. Several Pharmacological techniques have been used in order to reduce these responses, such as local anesthetic drugs, beta blocker, alpha-2 blocker, and vasodilator for instance. Fentanyl is one of the anesthetic potions which often used in order to decrease cardiovascular fluctuation. Aimed for getting optimal result from Fentanyl